PEMANFAATAN VOICE RECOGNITION PADA TELEPON GENGGAM BERBASIS ANDROID SEBAGAI KENDALI PERANGKAT ELEKTRONIK - Wahono, Yohanes; Harianto, Harianto; Wibowo, Madha Christian (Journal of Control and Network Systems, 2013)
Everyone is always busy with daily routine activities. For example, in the morning had to turn off the lights and turn on the lights in the evening. In general, the use of intermediaries cable to control electronic devices. Current technological developments in the field of advanced electronics, such as a wireless device that can replace the role of cable in controlling electronic devices. Android operating system has a voice input applications that is Google voice input. Google voice input is the default application from the Android operating system that can be used for various purposes such as for typing SMS and do an online search just with voice input. From the voice input technology, Android and wireless researchers want to create a system that allows an Android-based mobile phone to be used as control devices for controlling multiple electronic devices that contained electronic equipment in the home, such as lights, electronic door locks and fences with motor. With this system the routines of daily activities can be made ??more comfortable. Googles voice input will facilitate the use of Android-based mobile phone applications. In use of the device will be easier as only input sound without having to go where the control devices such as light switches.